Bearing My Heart: The Role of Extracellular Matrix on Cardiac Development, Homeostasis, and Injury Response - Silva, Ana Catarina; Pereira, Cassilda; Fonseca, Ana Catarina R. G.; Pinto-do-Ó, Perpétua; Nascimento, Diana S. (Frontiers in Cell and Developmental Biology, 2021)
The extracellular matrix (ECM) is an essential component of the heart that imparts fundamental cellular processes during organ development and homeostasis. Most cardiovascular diseases involve severe remodeling of the ECM, culminating in the formation of fibrosis that is deleterious to organ function. Treatment schemes effective at managing fibrosis and promoting physiological ECM repair are not yet at reach. Of note, the composition of the cardiac ECM changes significantly in a short period after birth, concurrent with the loss of regenerative capacity of the heart. This highlights the importance of understanding ECM composition and function headed for the development of more efficient therapies. In this review, we explore the impact of ECM alterations, throughout heart ontogeny and disease, on cardiac cells and debate available approaches to deeper insights on cell-ECM interactions, towards the design of new regenerative therapies.